Influência Parental no Desporto Adaptado: estudo centrado na perspetiva dos pais - Sara Castro Sousa (2018)
The present study aims to explore the parental influence in the disability sport context by evaluating the behaviour and motivational orientations of the parents. Specifically, it was intended to conduct a preliminary validation of parental behaviours questionnaire and of the motivational orientation questionnaire, through the analysis of the psychometric properties (i.e., internal consistency). In addition, the prevalence and associations between the different subscales of both questionnaires were analyzed. The comparative analysis in behavior perception and motivational orientation of the parents was also carried out according to the sociodemographic variables related to the parents (i.e., personal, school, sports) and with the athletes (i.e., sports, disability). 138 parents/relatives of athletes practicing different sports in the field of disability sport participated in the study. The participants completed a sociodemographic questionnaire, the Questionnaire on Parental Behaviors in Sport and the Questionnaire on Motivational Sports Orientation. The results showed that the instruments used are adequate to the context of parental influence in parents/relatives of athletes with disabilities. Technical influence, dissatisfaction with sports performance and ego orientation were highlighted as negative behavior related with parental suport. Variables such as age, level of education, type of sport and level of competition may interfere in the type of parental support and type of motivation exhibited by the parents. Moreover, further research is needed to deepen the relationships between parents / relatives and athletes from disability sport at national level.